The application of adhesive bonding for different types of material for car body parts - Muhammad Shahir, Nazir (2013)
The application of adhesive bonding as a new technology method to join car body parts shows the pace of development in automotive technology recent years. But, adhesive technology application used and advantages are not fully explored. This study deals with effectiveness of adhesive bonding as an alternative to spot weld to join car body parts and to investigate the tensile strength of the adhesive bonding based on the different material specification of varying thickness. Two types of joining method involve in this study which is adhesive bonding and spot weld. By joining two different materials with varying thickness, these two types of joining method are tested by undergoing tensile shear test for multiple specimens. Load/extension graph is plotted from data collected and result based on tensile shear strength is compared. From the study, adhesive bonding achieve higher tensile strength compared to spot weld with shear tensile strength up to 12.0847 MPa.